PENGARUH CAPITAL ADEQUACY RATIO, BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL, NON PERFORMING FINANCING, DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP PROFITABILITAS - Desy Sulistyawati (Universitas Slamet Riyadi, 2015)
Financial performance is an important thing for the company, since the banking business is a business of trust, then the bank must be able to demonstrate its credibility so that more people are transacting in the bank. One effort to improve public confidence is through increased profitability, the higher profitability of the bank, the better the company's financial performance. The study population was banking companies listed on the Stock Exchange in 2011 – 2013. Samples were taken by purposive sampling of 30 banks. The data source is a secondary data collected by the method of documentation. Methods of data analysis used multiple linear regression, the coefficient of determination (R2), test F and test t. Results of the research showed that the CAR has negative and not significant on ROA, Operating Expenses and Operating Income has significant negative effect on ROA, NPF has significant negative effect on ROA, CSR disclosure has positive and significant effect on ROA. Keywords: Capital Adequacy Ratio, Operating Expenses and Operating Income, Non Performing Financing, Corporate Social Responsibility and return on assets.